Spontaneous aortic pseudoaneurysm rupture into the sigmoid colon in Behçet’s disease patient - Lee, Su Lim (World J Gastroenterol, 2015)
Behçet’s disease (BD) is a multisystem autoimmune disorder characterized by recurrent orogenital ulcers, uveitis, and skin lesions. The vascular manifestations include thrombophlebitis, stenosis, occlusion, and pseudoaneurysm. BD infrequently precipitates aortic pseudoaneurysm rupture into the sigmoid mesocolon and lumen of the adjacent colon. Here we report an extremely rare case of spontaneous abdominal aortic pseudoaneurysm rupture via the sigmoid mesocolon into the lumen of the sigmoid colon in a 37-year-old patient with BD.